Entscheidende Situationen - entscheidende Kriterien Fallbeispiele aus neutestamentlicher Zeit als Orientierungshilfen für die Gegenwart = Decisive situations and decision criteria : exemplar cases from the era of the New Testament as guidelines for the present - Stowasser, Martin 1959- (2015)
The article investigates how New Testament authors used to manage conflicts and shows what criteria guided them. To this end, four situations of conflict in Early Christian communities are showcased. These are: Paul’s struggle for a universal horizon of Christianity leaving behind Jewish Law; the loss of plausibility in 2 Peter of the parousia of Jesus Christ; the process of enculturation traced in 1 Peter; and the conflict between orthodoxy and orthopraxis in 1 Cor regarding the private consumation of meat sacrificed in pagan temples.
Keywords: Bibel; Bibel; Frühchristentum; Konflikt; Thora; Parusie; Community life; criteria of decision; Conflict; Guidelines